Holistic Leadership in Elementary Character Education: Modelling, Habituation, and Integration in a Challenging Context - Inke Safitri; Meilia Rosani; Mahasir Mahasir (Yayasan Sembilan Pemuda Indonesia, 2026)
This study examines the implementation of holistic leadership in strengthening character education amidst the challenges of the digital era at SDN 17 Tungkal Ilir, Indonesia. Employing a descriptive qualitative approach, data were collected through in-depth interviews, field observations, and documentation analysis involving the principal, teachers, and community stakeholders. The findings reveal a three-tier strategic framework: first, the principal serves as the primary role model through a consistent “5S” culture (Greet, Smile, Salutation, Politeness, Courtesy), creating a ripple effect of integrity; second, character values are internalized through structured routines, including the “7 Habits of Happy Kids” program, daily reflection journals, and Scouting as a character laboratory for discipline and independence; third, the school establishes a “School Fortress” (Benteng Sekolah) by integrating formal partnerships with the Police and parents to mitigate external negative influences such as online gambling and gadget addiction. The study concludes that holistic leadership, which synchronizes exemplary behavior, consistent habituation, and cross-sectoral collaboration, effectively fortifies student character even within resource-constrained and technologically challenging environments. The novelty lies in the integrated framework combining role modeling, structured routines, and external partnerships as a unified response to digital-era moral risks. Practically, this model offers a replicable strategy for schools facing similar challenges. The study contributes to educational leadership literature by demonstrating how holistic leadership can transcend conventional teaching to address structural constraints and moral degradation risks in contemporary schooling contexts.